Discovery as culture, not template: lessons from Hungary - Dror, Keren (Teaching Mathematics and Computer Science, 2026)
In this study, I investigate the structural adaptations necessary to implement Hungarian-style guided discovery in mainstream secondary school classrooms. During a six-week residency in Budapest, I observed classrooms, interviewed five Hungarian educators, and collected survey and interview data from students. My findings suggest that guided discovery in Hungary is less a fixed method and more a pedagogical culture, shaped by shared values, historical influences, and professional communities. While Hungarian educators praised its ability to foster deep thinking, student agency, and creativity, they also described challenges around pacing, assessment, and curriculum alignment. Structural supports such as flexible curriculum frameworks, professional networks, and differentiated assessment practices emerged as critical enablers of the method’s success. Student responses revealed both the promise of discovery-based instruction and the pressures it can create without sufficient scaffolding. I conclude that Hungarian-style guided discovery is not best understood as a replicable model, but as a set of values that evolve through professional dialogue and trial-and-error. Its meaningful implementation depends not on uniform procedures, but on the presence of cultural, institutional, and community structures that allow teachers to make it their own. Subject Classification: 97D40, 97D50, 97C30